SUSTAINABILITY IN HAJJ AND UMRAH MANAGEMENT: EXPLORING ECO-FRIENDLY PRACTICES AND STRATEGIES - Rodiyah, Rodiyah (Jurusan Manajemen Dakwah, Fakultas Ilmu Dakwah dan Ilmu Komunikasi, UIN Syarif Hidayatulla, 2024)
This research explores the current sustainability practices in Hajj and Umrah management and identifies potential strategies and eco-friendly initiatives to reduce the environmental footprint of these large-scale religious events. hrough a comprehensive literature review, this study assesses the environmental impact of Hajj and Umrah, focusing on waste management, water conservation, and energy consumption. It also examines existing sustainability initiatives implemented by the Saudi government and other stakeholders and evaluates their effectiveness. The systematic literature review methodology includes determining research questions, identifying relevant sources, analyzing and synthesizing the literature, identifying gaps and opportunities, drawing conclusions, and making recommendations. The findings of this research contribute to the development of knowledge about sustainable Hajj and Umrah management and provide valuable insights for stakeholders involved in the planning and implementation of Hajj and Umrah, with the aim of reducing environmental impact